Kambo: A ritualistic healing substance from an Amazonian frog and a source of new treatments - Jan M Keppel Hesselink (Open Journal of Pain Medicine - Peertechz Publications, 2018)
Kambo is the name of a complex mixture of a number of bioactive peptides, secreted via the skin of a tropical frog, Phyllomedusa bicolor. Since centuries this secretion is harvested from the living animal by members of tribes living in the Amazonian forest, and applied to little wounds in the arms or legs, in orderto enhance hunting skills. Since some decades the use of this frog secretion has migrated to the West, is used in Kambo rituals and administered by Kambo practitioners to volunteers. The aim of the Kambo application is to heal or integrate, and sometimes to cure or lessen symptoms such as chronic pain, anxiety, depression, or chronic eczema. Apart from this ritualistic use, Kambo is identifi ed as a source for leads for new treatments, from antibiotics up to analgesics. We will briefl y review the Kambo ritual and discuss three important neuropeptides from Kambo with analgesic properties.